META-ANALISIS PENGARUH INTERVENSI VIRTUAL REALITY THERAPY UNTUK MENURUNKAN SOCIAL ANXIETY DISORDER - Jocelyn Faustina Santoso; Ananta Yudiarso (Jurnal Psikologi, 2023)
This study aims to see the effectiveness of appropriate virtual reality therapy methods to reduce level of social anxiety disorder in individuals. This research method is a meta-analysis based on the PRISMA-P 2020 procedure. This research involved 7 previous experimental studies that used virtual reality therapy as an intervention in reducing social anxiety disorder. The result of this study is that the virtual reality therapy method has a large effect size in reducing individual social anxiety disorder. Virtual reality therapy should be combined with other interventions such as cognitive behavior therapy (CBT) or mindfulness-based warm-ups and individuals are encouraged to do self-reflection to reduce the level of social anxiety disorder they experience.